Neighbourhood policing: the rise and fall of a policing model - Innes, Martin (Clarendon studies in criminology, 2020)
This work tells the story of how and why neighbourhood policing was originally developed, the ways it has been implemented across different communities and in respect of different crime problems, and what its future prospects are likely to be.